The Identification of Pisces at Ujungbatu Fish Auction in Jepara as a Source of Animalia Discovery-Based Handout - Aidah, Nur; Isnaeni, Wiwi; Yuniastuti, Ari (Journal of Innovative Science Education, 2018)
Jepara Regency has very large marine resources. Various species of fish including pelagic and demersal are a local potential that can be empowered as a source of science learning in the form of handout based on discovery learning. The use of discovery-based handout is expected to be able to improve cognitive learning outcomes and science process skills. This research is a development research specifically One Group Pretest-Posttest Design. As many as 18 species were obtained at the fish auction in Ujungbatu Jepara. The validation of subject-matter experts on the content of the handout was good and very good on language aspect. Assessment on language experts, media size, design and content was in a very good category. The effectiveness of handouts from N-Gain result was obtained an average score of 0.4 which was in the medium category. While science process skills gained an average score of 81% in the good category. The practicality of the handouts was derived from student responses.  An aspect called significance was considered very good. Other aspects such as ease understanding, learning interes and presentation were good. While students’ enthusiasm was in good enough category. The practicality of the handouts from teacher responses include some aspects in terms of ease understanding, students’ enthusiasm, learning interest, presentation and the significance were in a very god category. It can be concluded that the use of discovery-based handout in learning Pisces material is effective and practical to improve students’ cognitive learning outcomes and science process skills both individually and classical.